PAEBES: modos, formas e diálogos a partir dos usos dos resultados em língua portuguesa da avaliação externa estadual no município de Cariacica-ES - Pereira, Selma Lúcia de Assis (2015)
This work includes studies by research line Education and Languages (verbal), the Program of Graduate Studies in Education of the Federal University of Espirito Santo. It is a qualitative research, structured in the form of case studies, themed external evaluation. Focuses on Education Assessment Program Basic of the Holy Spirit ( PAEBES ) from documentary sources and interviews by Portuguese teachers of state schools in the city of Cariacica – ES. The objective of the study is to investigate dissemination strategies of the results of Portuguese Language adopted by PAEBES and uses that are made of the results at the state network of schools of Cariacica-ES municipality to understand modes and forms of dialogue between the external evaluation and different subjects responsible for student learning in Portuguese. We understand that the theoretical perspective of Bakhtin (2003) on dialogism / polyphony and the theoretical perspective of Certeau (2005) on the reinvention of everyday life contributed to the analysis of language speeches. The analysis pointed out that there are many speeches , many " voices " and " way of doing " in dialogue with the results of the program by teachers of Portuguese Language teachers and principals. These ways of doing are " invented " and " reinvented " by creativity, criticality and inventiveness of these subjects and do not conform to the postulates by appropriation workshops of program results.